PERANCANGAN SISTEM KERANGKA PENILAIAN KINERJA MANAJER OPERASIONAL MENGGUNAKAN PENDEKATAN BALANCED SCORECARD PADA PT PEGADAIAN (PERSERO - Mahendra, Irfan (Jurnal Pilar Nusa Mandiri, 2012)
Pegadaian is a State Owned Enterprises (SOEs) is engaged in financing, with the main business is pawning services. The level of competition in the mortgage sector is currently very tight and will continue to increase the complexity and intensity. Further pawnshop must continually improve its performance, that the company competitive advantage can be realized. An important factor to consider in this case is the performance appraisal system, because the objective performance appraisal system, comprehensive, and continuous performance of the company will continuously be reviewed and could be improved. The performance appraisal system has been used in Pegadaian is to use the merit system approach. This approach is considered highly subjective and may not represent actual employee performance. Another approach that is popular and widely used is the assessment of performance using a balanced scorecard approach, which is a strategic management system that can be used to assess the company's performance objectively and comprehensively. This research is to design a framework for appraisal the performance of the employee (System Operations Manager) uses a balanced scorecard approach to the IT Operations Division of Pegadaian. Design framework for assessing performance using the balanced scorecard approach is done through two main stages, design scorecard for the mission center which then cascaded into team and personal scorecard.